The next generation Front-End Controller for the Phase-I Upgrade of the CMS Hadron Calorimeters. (1st March 2017) - Costanza, F.; Behrens, U.; Campbell, A.; Karakaya, T.; Martens, I.; Melzer-Pellmann, I.A.; Sahin, M.O.
Abstract: The next generation Front-End Controller (ngFEC) is the system responsible for slow and fast control within the Phase-I Upgrade of the CMS Hadron Calorimeters. It is based on the FC7, a μ TCA compatible Advanced Mezzanine Card developed at CERN and built around the Xilinx Kintex ® -7 FPGA. The ngFEC decodes the 40.0788 MHz LHC clock and the synchronization signals received from the backplane and distributes them to the front-end electronics through six GBT links. The latency of the fast control signals is fixed across power cycles. Even if the direct link to a front-end module is broken, a redundancy scheme ensures a successful communication using the link to the neighboring front-end module. Thanks to the ngFEC all front-end modules can be remotely programmed using the JTAG standard protocol. The CCM server software interfaces the ngFEC to the Detector Control System which constantly monitors voltages and temperatures on the front-end electronics. This document reviews the characteristics and the development status of the ngFEC.